Hemoptisis pada Pasien Aspergilloma Paru Kiri: [Hemoptysis in Aspergiloma Patient: A Case Report] - Gilang Muhammad Setyo Nugroho; Laksmi Wulandari (Faculty of Medicine Universitas Airlangga, 2018)
Background: Aspergilloma is a fungus ball (misetoma) that occurs because there is a cavity in the parenchyma due to previous lung disease. This fungus ball can move inside the cavity but does not invate the cavity wall. The presence of fungus ball causes recurrent hemoptysis. Case: We present a 45-year-old female patient with left lung Aspergilloma. Diagnosis of Aspergilloma was based on histopathology from FNAB CT guiding of left pulmonary which showed Aspergillus. Patient was treated with left superior lobe lobectomy at the hospital. The examination result of anatomical patology obtained from lung tissue was aspergillosis, from GeneXpert examination lung tissue showed positive MTB with rifampisin sensitive. Post-operative condition of the patient was stable, surgical wound improved, took off drain patient. There were clinical improvements after the surgery. Discussion: Diagnosis of Aspergilloma was based on clinical, radiology, and microbiology. Aspergilloma with severe symptoms (hemoptysis massive with life-threatening or other complications that require more than 1 time hospitalisation) and good physical condition should undergo surgical therapy in the form of lobectomy in accordance with the extent of lung abnormalities. Patient got first category anti tuberculosis drugs for 6 months and fluconazole for 2 months. Conclusion: It is necessary to consider the suspicion of Aspergillus infection, in patient with history of previous tuberculosis accompanied by a history of recurrent hemoptysis. Patient with reccurent hemoptysis and good physical condition should undergo surgical therapy.